EVALUASI PENYEBARAN INFORMASI PADA PROSES REKONSTRUKSI PASCA BENCANA ALAM DI KOTA PALU - ANDI AKIFAH,; RISQY ALFIYATY,; KUDRATULLAH, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
After the earthquake, tsunami and liquefaction on 28 September 2018 which devastated Palu City, parts of Sigi and Donggala Regencies, chaos occurred which was triggered by limited access to information and uncoordinated sources of information resulting in confusion of information. This study aims to evaluate the dissemination of information about the post-disaster reconstruction process on 28 September 2018. This research is expected to become a reference for stakeholders in terms of delivering policies to the public so that there is no resistance in disaster-affected communities. This study uses a qualitative approach based on case study research. The results of the study show that the post-natural disaster reconstruction that occurred in Palu City on September 28, 2018 aims to restore the motivation of people's lives for the better. Information related to reconstruction is disseminated in various ways, starting from the central government, regional governments such as the Public Works and Public Housing (PUPR) Office, Regional Disaster Management Agency (BPBD), village officials, and foundations that donate to the sub-district head, village head, RT/ RW and community leaders who have a closer emotional relationship with the community. The information received is properly evaluated through a deliberation process by the community and the government. The media used in the process of disseminating information is through WhatsApp groups, loudspeakers and face to face.